Cyclic Nucleotide Phosphodiesterases: important signaling modulators and therapeutic targets. (12th September 2014) - Ahmad, F; Murata, T; Shimizu, K; Degerman, E; Maurice, D; Manganiello, V
Abstract : By catalyzing hydrolysis of cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP), cyclic nucleotide phosphodiesterases are critical regulators of their intracellular concentrations and their biological effects. As these intracellular second messengers control many cellular homeostatic processes, dysregulation of their signals and signaling pathways initiate or modulate pathophysiological pathways related to various disease states, including erectile dysfunction, pulmonary hypertension, acute refractory cardiac failure, intermittent claudication, chronic obstructive pulmonary disease, and psoriasis. Alterations in expression of PDEs and PDE‐gene mutations (especially mutations in PDE6, PDE8B, PDE11A, and PDE4) have been implicated in various diseases and cancer pathologies. PDEs also play important role in formation and function of multimolecular signaling/regulatory complexes, called signalosomes. At specific intracellular locations, individual PDEs, together with pathway‐specific signaling molecules, regulators, and effectors, are incorporated into specific signalosomes, where they facilitate and regulate compartmentalization of cyclic nucleotide signaling pathways and specific cellular functions. Currently, only a limited number of PDE inhibitors (PDE3, PDE4, PDE5 inhibitors) are used in clinical practice. Future paths to novel drug discovery include the crystal structure‐based design approach, which has resulted in generation of more effective family‐selective inhibitors, as well as burgeoning development of strategies to alter compartmentalized cyclic nucleotide signaling pathways by selectively targeting individual PDEs and their signalosome partners.